1990
DOI: 10.1099/00221287-136-2-233
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polyamine biosynthesis inhibitors on mycelial growth, enzyme activity and polyamine levels in the oat-infecting fungus Pyrenophora avenae

Abstract: The fungus Pyrenophora avenae, an important pathogen of oat crops, was grown on solid and liquid media containing the polyamine b p t h e s i s inhibitors difluoromethylomithine (DFMO), methylglyoxal bdguanylhydrazone) (MGBG), ethylm@ylglyoxal bis(guanylhydraz0ne) (EMGBG) + / -polyamines. All of the compounds inhibited mycelial growth i f the fungus. MGBG and EMGBG were more effective than DFMO. The addition of putresine and spermidine almost completely prevented inhibition of mycelial growth by DFMO. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 22 publications
2
26
1
Order By: Relevance
“…Following that historical study, the requirement was confirmed in many polyamine-auxotrophic mutants of Escherichia coli and Saccharomyces cerevisiae (153). Thereafter, numerous studies on the growth inhibition of phytopathogenic fungi (30,99,126,147,(165)(166)(167) or yeast (91,120) were conducted using specific inhibitors of polyamine biosynthesis. In most cases, the inhibition can be completely reversed by the addition of Put or Spd, confirming the essentiality of polyamines for the growth of fungal hyphae (125).…”
Section: Polyamines and Rhizobial Growthmentioning
confidence: 99%
“…Following that historical study, the requirement was confirmed in many polyamine-auxotrophic mutants of Escherichia coli and Saccharomyces cerevisiae (153). Thereafter, numerous studies on the growth inhibition of phytopathogenic fungi (30,99,126,147,(165)(166)(167) or yeast (91,120) were conducted using specific inhibitors of polyamine biosynthesis. In most cases, the inhibition can be completely reversed by the addition of Put or Spd, confirming the essentiality of polyamines for the growth of fungal hyphae (125).…”
Section: Polyamines and Rhizobial Growthmentioning
confidence: 99%
“…Yeasts, Neurospora crassa and Aspergillus nidulans (Tabor & Tabor, 1985) as well as some phytopathogenic fungi, especially rusts (Foster & Walters, 1990) do not have ADC, and synthesize putrescine by ODC only. However, other phytopathogenic fungi have active ADC (Khan & Minocha, 1989) and Zarb & Walters (1994b) gave evidences of ADC activity in Laccaria proxima.…”
Section: mentioning
confidence: 99%
“…The reaction mixture (total volume of 150 ,uL) contained 20 ,L of enzyme, 120 gL assay buffer, and 10 gL of 0.5% (w/v) FTC-casein.…”
Section: Assay Of Proteolytic Activitymentioning
confidence: 99%
“…Polyamines have been implicated in a range ofphysiological plant responses (20,22). The possible involvement of polyamines in the transduction of the viroid pathogenic signaling has also been hypothesized (14).…”
Section: Introductionmentioning
confidence: 99%